A Review Disaster Mitigation of Jakarta Land Subsidence Areas - Putri, R.F. (EDP Sciences, 2021)
The Jakarta Capital Special Region of Jakarta is an area in the Java Island that has the highest level of vulnerability to land subsidence disasters. Land subsidence is caused by several factors such as excessive use of groundwater and natural compression of soil conditions. This study used a review analysis method based on a literature study on mitigation of land subsidence disasters in Jakarta city. The mitigation planning of land subsidence disasters in Jakarta will refer to government regulations on disaster management and Jakarta City spatial planning. Disaster mitigation is necessary to anticipate or reduce disaster risk. Disaster mitigation is a series of efforts to reduce disaster risk through physical development combined with awareness and capacity building in dealing with disaster threats. Education cannot be separated from the active role of the community and local government. High-densely populated areas will lead to more use of groundwater in Jakarta city. The excessive use of groundwater has resulted in more intensive land subsidence in Jakarta's urban area. The safe zone mapping of subsidence disasters is prominent to reduce and control land subsidence disasters. The government's efforts to lessen the impacts of land subsidence are by educating the population in disaster areas. Â© The Authors, published by EDP Sciences.